2020
DOI: 10.1261/rna.074393.119
|View full text |Cite
|
Sign up to set email alerts
|

Splicing conservation signals in plant long noncoding RNAs

Abstract: Long non-coding RNAs (lncRNAs) have recently emerged as prominent regulators of gene expression in eukaryotes. LncRNAs often drive the modification and maintenance of gene activation or gene silencing states via chromatin conformation rearrangements. In plants, lncRNAs have been shown to participate in gene regulation, and are essential to processes such as vernalization and photomorphogenesis. Despite their prominent functions only over a dozen lncRNAs have been experimentally and functionally characterized.S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Therefore, other features independent of the integrity of transcripts, such as MLCDS (the most-like coding domain sequence) and k-mers, were applied in lncRNA identification. In addition, lncRNA shows a distinct difference from mRNA in terms of sequence conservation, which can be measured from multiple sequence alignments (Corona-Gomez et al 2020). In brief, the exons of lncRNAs are far less conserved than the exons of mRNAs (Ulitsky 2016;Hon et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, other features independent of the integrity of transcripts, such as MLCDS (the most-like coding domain sequence) and k-mers, were applied in lncRNA identification. In addition, lncRNA shows a distinct difference from mRNA in terms of sequence conservation, which can be measured from multiple sequence alignments (Corona-Gomez et al 2020). In brief, the exons of lncRNAs are far less conserved than the exons of mRNAs (Ulitsky 2016;Hon et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These lncRNAs are enriched in certain QTLs (Quantitative Trait Loci) containing genes regulating stress‐receptive pathways (Yuan et al, 2018). lncRNAs have important roles in the modulation of nutrient uptake, growth and development of plants, adaptation of resistance capability against disease and various environmental stresses, regulating some biological activities via modification of histone and chromatin disposition in plants (Corona‐Gomez et al, 2020; Nejat & Mantri 2018; Sun et al, 2020). Chen, Shi, et al (2018) demonstrated that lncRNAs regulate the expression of genes related to various amino acids metabolic pathways (phenylalanine, methionine, and cysteine), photosynthetic metabolism, and phenylpropanoids metabolic pathways to reduce the cadmium toxicity in rice.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…MaxEntScan is based on maximum entropy distribution and is considered to offer the most unbiased approximation for modeling short sequence motifs [49]. Remarkably, it considers dependencies between both nonadjacent and adjacent positions and is used extensively in analyses of lncRNA splice-site conservation [50][51][52]. One such study was performed on vertebrate lncRNAs [50], in which multiple sequence alignment together with transcriptomics data were utilized to determine the homologous positions in splice sites, leading to the construction of a comparative map of splice sites.…”
Section: Conservation Of Splicing Signalsmentioning
confidence: 99%
“…The authors showed that in conserved human transcripts, 87% of splice sites are present in other species, including mice, rats, cows, and dogs, yet most of the novel splice sites originated during primate evolution. MaxEntScan has also been used in recent studies on lncRNA splicing conservation in 16 Brassica species [ 52 ]. These studies revealed that nearly 18% of lincRNAs display splicing conservation in at least one exon in Brassicaceae plant family members.…”
Section: Conservation Of Splicing Signalsmentioning
confidence: 99%